Emergency handling system - Kamat, Maznah (Faculty of Computer Science and Information System, 2008)
The current emergency handling services are cumbersome; a caller needs to dial 999 in order to report an emergency. In most occasions civilians are urged to call an emergency centers, which normally not remembered by many. The distance between the occurrence of the incident and the center remains as the major aspect for instant assistance. An assistance may not able to reach at soonest time if caller fail to describe his/her exact location. Worst of all the current system hinders handicapped from reporting an emergency. The advancement in wireless technology and infrastructure has amplified the usage of cell phone in our lives, therefore a location-based ah hoc emergency handling system is a value-add to the 999 service. This research studies the issues in providing an emergency handling system (EHS), which deploys location based technology that will detect the location of a caller and connect to database server that store required data. The system enable user to forward distress message either to police station, rescue team, hospital and etc. The professional application checks an emergency message, view location of an incident and respond to an emergency request. The system employs CGI+TA technique in determining the locations of caller and the nearest professional within the incident vicinity. In addition, every message that is transmitted through the network in encrypted and authenticated to ensure integrity and authenticity of an emergency call. This research shows that EHS has several advantages over current emergency services, and beneficial to handicapped.